A simplified model for whole-body angular momentum calculation. (January 2023) - Liu, Ming; Naseri, Amirreza; Lee, I-Chieh; Hu, Xiaogang; Lewek, Michael D.; Huang, He
Highlights: A simplified rigid body model to calculation of full body angular momentum. Only 7 IMU sensors are needed to calculate the full body angular momentum using this simplified model. The model was validated on both able-bodied subjects and transfemoral amputees. Abstract: The capability to monitor gait stability during everyday life could provide key information to guide clinical intervention to patients with lower limb disabilities. Whole body angular momentum ( Lbody ) is a convenient stability indicator for wearable motion capture systems. However, Lbody is costly to estimate, because it requires monitoring all major body segment using expensive sensor elements. In this study, we developed a simplified rigid body model by merging connected body segments to reduce the number of body segments, which need to be monitored. We demonstrated that the Lbody could be estimated by a seven-segment model accurately for both people with and without lower extremity amputation.